Assessing and mapping electricity access patterns in a developing country - N.T. Mbungu; K.D. Milambo; M.W. Siti; R.C. Bansal; R.M Naidoo; T.P. Kamabu; F.T. Kiseya; D.H. Tungadio; M.K. Kayembe; B.B. Banza (Energy Reports, 2023)
Despite low electricity access rates and weakened electricity sector governance under the pressure of population growth, modes of access to electricity in Lubumbashi vary spatially and in their typologies. However, to date, there is no detailed information on mapping households’ modes of access to the National Electricity Company (SNEL) electricity network. This study aims to assess and map both formal and informal methods of household access to electricity in Lubumbashi. A socio-technical survey was conducted among 1211 households in the 7 communes or districts of the city. The results showed that the electricity access rate in the different districts of Lubumbashi varies between 41.6 and 78.3%, with an urban average of 63.8 %. The lowest rate is observed in the Annex district, while the highest is kept in the Kamalondo commune. At both the rural and urban levels, the most dominant method of access to electricity is a connection to the grid (formal and legal methods), with the highest rate in the Kamalondo, Kenya and Lubumbashi districts. Clandestine electrical connections are most common in the communities of Kamalondo and Kenya. The Annexe and Lubumbashi districts have the lowest rates of illegal electric connections. This study showed that the spatial distribution of cases of electricity theft and non-payment of bills in Lubumbashi is influenced by complex factors, such as the interaction between urban growth, household income level and the governance mode. The fight against fraudulent connections should be based on the present study to propose localized and adequate solutions in the different districts.